Functions of Sphingolipids in Pathogenesis During Host–Pathogen Interactions - Wang, Jian; Chen, Yi-Li; Li, Yong-Kang; Chen, Ding-Kang; He, Jia-Fan; Yao, Nan (Frontiers in Microbiology, 2021)
Sphingolipids are a class of membrane lipids that serve as vital structural and signaling bioactive molecules in organisms ranging from yeast to animals. Recent studies have emphasized the importance of sphingolipids as signaling molecules in the development and pathogenicity of microbial pathogens, including bacteria, fungi, and viruses. In particular, sphingolipids play a key role in regulating the delicate balance between microbes and hosts during microbial pathogenesis. Some pathogens, such as bacteria and viruses, can harness host sphingolipids to promote development and infection, whereas both host and pathogen sphingolipids are involved in fungus–host interaction. Moreover, a regulatory role for sphingolipids has been described, but their effects on host physiology and metabolism remain to be elucidated. Here we summarize the current state of knowledge about sphingolipid functions during pathogenesis and interactions with host factors, including how sphingolipids modify pathogen and host metabolism, with a focus on pathogenesis regulators and relevant metabolic enzymes. In addition, we discuss emerging perspectives on sphingolipids in host–microbe interactions as new therapeutic strategies for infectious diseases.